Relationships between attitude, self-efficacy and inclusive teaching practices. The mediating role of social teacher support - Cebreros-Valenzuela, Daniela (2024)
Introduction: Teachers play an essential role in inclusive education, which proposes an educational model where all students can learn, participate, and feel welcome in universities. Objective: Examine the direct and indirect relationships between teaching attitudes towards inclusion, perception of teaching self-efficacy for inclusion, social support, and inclusive teaching practices towards university students with disabilities. Method: In this study participated 401 teachers assigned to five public universities in Sonora, Mexico (51.4% female) aged between 24 and 69 years (M age = 46.76, SD = 11.51 years) who answered several self-report scales. A structural model was calculated with latent variables, with attitude and self-efficacy as input variables, social support as a mediating variable, and inclusive teaching practices as an outcome variable. Results: indicate that the variables considered in the model explain a significant part of the variance in inclusive teaching practices (R2 = .36). Teaching attitudes are not directly related to inclusive teaching practices but are indirectly related to their association with social support. For its part, self-efficacy is directly and indirectly related to inclusive teaching practices. Discussion: It is shown that the characteristics of teachers are associated with the frequency with which they carry out inclusive practices for students with disabilities. The practical consequences and limitations of the study are discussed